Analisis Makna Quarter Life Crisis Dalam Lirik Lagu Bts “Zero O’clock” (Kajian Semiotika Ferdinand De Saussure) - Wardani, Indah Kusuma; Yuwono, Andri Prasetyo (Jurnal Ilmiah Wahana Pendidikan, 2024)
Music is part of communication, through song lyrics the communicator tries to convey a message to the communicant. If you look at the lyrics, music is a form of verbal communication. BTS (Beyond The Scene) or also often known as Bangtan Sonyeondan, is a male singer group from South Korea. BTS is one of the singers who uses music as a medium for conveying messages to their listeners and packages them through song lyrics that hold special meaning. This research is entitled "Analysis of the Meaning of Quarter Life Crisis in the Lyrics of the BTS Song "Zero O'Clock" (Ferdinand De Saussure's Semiotic Study)". This research aims to find the meaning of Quarter Life Crisis contained in the lyrics of the BTS song "Zero O'Clock". Using Ferdinand De Saussure's semiotic theory, the author examines the signifiers and signifieds in each verse of the BTS song entitled "Zero O'Clock" using a qualitative descriptive method. The result of this research is the discovery of the meaning of quarter life crisis contained in the lyrics of the BTS song "Zero O'Clock. Apart from the meaning of the quarter life crisis, BTS also has a motivational message for its listeners in this song entitled "Zero O'Clock".